Corticosterone regulates fear memory via Rac1 activity in the hippocampus. (September 2016) - Gan, Ping; Ding, Ze-Yang; Gan, Cheng; Mao, Rong-Rong; Zhou, Heng; Xu, Lin; Zhou, Qi-Xin
Highlights: Stress generates fear-specific memories and G-protein Rac1 may play a role in this. Stress and exogenous corticosterone downregulated activity Rac1. RU38486, glucocorticoid receptor agonist, recovered activity Rac1 and decreased memory. The glucocorticoid receptor inhibitor NSC23766 increased fear memory retrieval. Rac1 may thus be therapeutic targets in stress and memory disorders. Abstract: Stressful events can generate enduring memories, which may induce certain psychiatric disorders such as post-traumatic stress disorder (PTSD). However, the underlying molecular mechanisms in these processes remain unclear. In this study, we examined whether the active form of the small G protein Rac1, Rac1-GTP, is involved in fear memory. Firstly, we detected the time course changes of Rac1-GTP after foot shocks (a strong stressor) and exogenous corticosterone (CORT) treatment. The data showed that stress and CORT induced the downregulation of Rac1-GTP in the hippocampus. Changes in the serum CORT level were negatively correlated with the level of Rac1-GTP. Additionally, a glucocorticoid receptor antagonist, RU38486, not only recovered the expression of Rac1-GTP but also impaired fear memory. Furthermore, systemic administration of NSC23766, an inhibitor of Rac1-GTP, improved fear memory at 1.5 and 24 h. Therefore, Rac1 activity plays a critical role in stress-related cognition and may be a potential target in stress-related disorders.